The dominance of commercial ADYs and their correlation between fungal diversity, volatile compounds during industrial fermentations of Cabernet Sauvignon wines - Mengyan Wang; Xiaojing Huang; Jinwen Zhou; Yanlin Liu; Yun Bai; Yue Sun (Food Chemistry: X, 2025)
During the winemaking process, the dominance of commercial active dry yeasts (ADYs) influence the interactions among microorganisms and the profiles of wine aroma. In this study, the implantation percentage of ADYs, fungal diversity and volatile profiles during the industrial Cabernet Sauvignon wine fermentation from four wineries in Ningxia, China were investigated. Four species were identified by the culture-dependent method. A total of 38 volatile aromas were identified through headspace solid phase microextraction gas chromatography mass spectrometry. Interdelta sequence typing showed that FX10 strain used in Winery2 had a lower implantation percentage than that of IONYS-WF strain used in Winery4 during fermentation. High-throughput sequencing further elucidated differences in fungal community structures at different fermentation times between Winery2 and Winery4. Correlation analyses between microbial communities and flavor components highlighted the role of dominant species in shaping characteristic flavor profiles. This study deepens comprehension of how ADYs influence fungal succession and wine characteristics.